Leadership Capacity and Competency and Systematic Governance Failures in Motorcycle Transport Safety in Kenyan Cities - Ngeso , Cosmas Jagongo; Were, Susan; Ombui, Kepha (Human Resource and Leadership Journal, 2026)
Purpose: Road traffic crashes currently stand out as one of the key challenges facing both developed and developing countries. Kenya has in the recent decades experienced an alarming rise in the number of people who lose their lives along the roads. This situation has been aggravated by the emergence of motorcycles as a means of commercial transport in Kenya. While attempts have been made by the Kenya government to address existing motorcycle safety challenges, no significant attempt has been made to address systematic governance failures in motorcycle transport safety challenges from a governance perspective. This study therefore sought to determine the influence of leadership capacity and competency on systematic governance failures in motorcycle transport safety in Kenyan cities. Methodology: The study was conducted in Kenya’s cities (Nairobi, Mombasa and Kisumu) adopted a descriptive and cross-sectional survey research design. The target population was 266,049 motorcycle riders in the three Kenyan cities. The sample size was determined by use of Fisher formula involving cluster and simple random sampling method to select 384 respondents. The study used primary data, collected by use of semi-structured questionnaires. A pilot study was done to test the validity and reliability of the questionnaire. Data was analyzed using both descriptive and inferential statistics with the help of SPSS version 26.0. Quantitative data was summarized and presented in tables, charts and graphs. Findings: Based on the research findings, the regression findings affirmed that Leadership capacity and competency (β=0.275, p=0.000) has a positive and significant effect on systematic governance failures in motorcycle transport safety in Kenyan cities. Unique Contribution to Theory, Practice and Policy: The government should ensure that visible sign boards directing the motorists on the actions to take while on different roads. The Boda boda groups/leaders should collaborate with the leaders and well-wishers to help in constructing Boda boda shades. The county government should also ensure that the motorists have a secluded place to avoid harassments from the county officers.